Hasil belajar materi lingkaran siswa sekolah dasar dengan menerapkan model pembelajaran kooperatif STAD - Kartika Eka Sari Sinaga; Mahdalena Mahdalena; Suwanto Suwanto (Journal of Didactic Mathematics, 2022)
The problem in this study regarding learning mathematics is the low student learning outcomes because the appropriate method is not used in learning, which causes the teaching and learning process to be less than optimal. This is evidenced by the fact that only 13 students (48.14%) of the 27 students were able to achieve the KKM score. The purpose of this study was to improve the results of learning mathematics in circle material by applying the STAD cooperative model to class VI students at SDN 002 Bagan Besar Dumai. The type of research used is classroom action research (CAR). The research was carried out in two cycles, each cycle going through four stages: planning, implementing learning improvements, collecting data, and reflecting. Based on the stages of the research conducted, it was found that the percentage of student learning outcomes in cycle I was 70.74%, increasing to 84.07% in cycle II. Thus, it can be concluded that the application of the STAD cooperative learning model can improve mathematics learning outcomes in circle material for students at SDN 002 Bagan Besar Dumai in the 2022-2023 academic year.